CONSIDERAÇÕES ACERCA DA INTERPRETAÇÃO E PRIMEIRAS IDEIAS SOBRE UMA TEORIA DA DECISÃO (Revista Direito em Debate, 2020)
This article has as its object the constitutional interpretation. It addresses the issue of law and the interpretation of rules in the context of judicial discretionarity. It takes into account the creation of a rational and coherent method for formatting decisions, especially in difficult cases. As a result, it is possible, from the texts of Hesse, Dworkin, Moreso and Bulygin, to understand how discretions should be in the narrow sense, below the Constitution, considering the most important properties and enabling the creation of the right from preexisting notions. The research methodology used was bibliographic and the hypothetical deductive method was used. The conclusion is that decision theory is necessary to understand discretionaty as a creative activity, but with the attribution of rationality, coherency with legal criteria and respect for historical and social aspects.
Keywords: Judicial discretionarity; Rational interpretation; Decision theory